Anna Yemelianenko, Philosophical foundations of existential theology (anthropological, ontological and epistemological aspects). Kyiv, Autograph, 2018, 384 р., ISBN 978-966-8349-10-2 - Shkribliak, Mykola (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2018)
The reviewed text reproduces one almost from the first attempts to systematically study the philosophical foundations of the so-called existential in Russian religious studies, or, as G. Emelianenko claims, rather, existential theology, which has recently been considered as a special direction of Christian theology. In the domestic religious studies this direction monographically only in the past, in 2017 was presented to scientists from the Institute of Philosophy. Shevchenko, who in his book "Christian Theology and Existentialism" tried to argue that the methodological tools used by K. Raner, J. Maritain, R. Bultmann, J. Macquarrie, H. A. Slaate, M. Westphal and many other foreign thinkers, allow us to qualify the theological concepts and teachings that they created as "existential theology," and the latter as a separate, rather specific, trend of modern theological thinking. In the concept of Shevchenko, "existential theology" is also presented in a narrower sense-first of all, as R. Bultman’s practice in the existential-hermeneutic interpretation of the texts of Holy Scripture is determined, in fact, by existential theology by the Anglican theologian J. Macquarrie. The monograph G. D. Emelianenko, on the one hand, continues the research of S. L. Shevchenko, asserting both its legitimacy and its relevance, and, on the other hand, implicitly and raises the question of the legitimacy and truth of the concept of Shevchenko, since demonstrates that a whole series of concepts, which are regarded as exemplary analogues of the so-called existential theology, in reality do not have a single, common "theoretical basis." It was the latter that was formulated in one of the questions arising after acquaintance with the text of G.D. Emelianenko’s monograph: "Is it worthwhile, instead of the creators of the above-mentioned concepts, to invent for them also some additional definitions, bringing them closer to the existentialist tradition?"